Prevalens av Sarcoptes scabiei hos thailändska gatuhundar - Fant, Daniel (2005)
The aim of present study was to evaluate the prevalences of Sarcoptes scabiei in Thai stray dogs. The study was performed in Pattaya, Thailand, and included 62 stray dogs, all cross-breeds. Degree and type of skin lesions, and presence of macroscopic ectoparasites were recorded for each individual. Blood samples were collected to determine the seroprevalences of IgG-antibodies against S. scabiei with ELISA. From 57 of the 62 dogs, two skin scrapings each were collected. The skin scrapings were treated with 10% KOH and examined with microscope for the presence of S. scabiei. The seroprevalence was 76% in the study population, which shows that S. scabiei is very frequent in stray dogs in Thailand. There was no difference in seroprevalences between the sexes, while the seroprevalence was significantly lower in young dogs (46%) than in adult dogs (84%). The seroprevalence of dogs with skin lesions were significantly higher than the seroprevalence of dogs without skin lesions (65% and 11% respectively). Macroscopic ectoparasites such as ticks, lice and fleas can cause similar skin lesions as S. scabiei, and were found on 46 (74%) of the dogs. Demodex canis was found in five (8.8%) of the dogs. S. scabiei was found in the skin scrapings from only one dog (1.8%). It is well known that skin scraping is an uncertain method for detection of S. scabiei. Considering this and the high seroprevalence, the results of the skin scrapings in the present study is probably an underestimation of the true prevalence.